Implikasi Pembuatan Akta Pelepasan Hak Pengelolaan Sebagai Perluasan Kewenangan Notaris Dalam PP Nomor 18 Tahun 2021 - Widyanti, Ni Komang Anggi; Priyanto, I Made Dedy (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
Examining and assessing the implications of the release of management rights made by and in the presence of authorized officials as an extension of the Notary's authority in PP No. 18 of 2021 is the purpose of writing this article. It was studied using normative legal research methods because the main object of the study was norms related to making deeds of relinquishment of management rights, which were supported by statutory and conceptual approaches. The primary legal material for the study is in the form of statutory regulations, which are supported by secondary legal material in the form of books and scientific articles related to management rights, authentic notary deeds, and the expansion of notary authority, which are collected using literature study techniques using descriptive and argumentative analysis techniques. As for the results of the study that has been carried out, it was found that there is a conflict of norms regarding the regulation of making a deed of release of management rights made by and before an authorized official, one of which is a Notary, with an authentic deed in Article 1868 of the Civil Code and UUJN-P. There are different responsibilities and legal consequences for deeds made by, and deeds made before a Notary, so it is not appropriate if these two elements are fulfilled. By using the principle of legal preference, the provisions in PP No. 18 of 2021 can be set aside by provisions in the Civil Code and UUJN-P.